Computer organization and design : the hardware/software interface (Morgan Kaufmann series in computer architecture and design., 2014)
"Presents the fundamentals of hardware technologies, assembly language, computer arithmetic, pipelining, memory hierarchies and I/O"--Provided by publisher.